Tindakan Penanggulangan Bencana Secara Berkelanjutan - (Jurusan Teknik Mesin Politeknik Negeri Semarang), Bondan Wismnadanikung,; (Jurusan Teknik Sipil, Fakultas Teknik Sipil, Universitas Islam Sultan Agung), Tri Hardono (Teknis, 2014)
Philosophically, sources potencial disaster accur from the natural activities of hydrological cyclus and vulcanical / tectonical (such as flood, earthquake, landslide, tsunami, vulcano eruption and so on) and human activities. Interaction in between natural and human will cause the magnitude of the disaster in various effects. How will the human and stake holder respond and prepare for the impacts of the disaster depend on the humans themself. Emergency operation and disaster relief action would be largerly concerned with the planning phase of disaster preparedness and should be done by all the stake holder and also necessary to be back up by legislative at national, regional and local levels to enable such planning to proceed, the warning communication, preparation for disaster fighting and for evacuation of people from danger areas. This writes is concerned with emergency phase when preparedness plans are brought into action. There are two main particular components, which are: 1. Emergency Operation involving the whole organization for disaster preparedness with all stake holder concerns and 2. Disaster Relief covering the action to be taken in order to bring relief to stricken areas. It is convinient to consider these two components separately although they are in fact highly independent. Both components will be described in their own settings represent the fullfilment of planning in the aim of sustainable achivement..Key Word : emergency operation and disaster relief, stake holder respond and preparedness.